Angiographic outcomes in the PLATO trial (Platelet Inhibition and Patient Outcomes) - Kunadian, Vijay; James, Stefan K.; Wojdyla, Daniel M.; Zorkun, Cafer; Wu, Jinhui; Storey, Robert F.; Steg, Ph. Gabriel; Katus, Hugo; Emanuelsson, Hakan; Horrow, Jay; Maya, Juan; Wallentin, Lars; et al. (JACC Cardiovascular interventions, 2013)
Objectives - The PLATO (Platelet Inhibition and Patient Outcomes) angiographic substudy sought to compare the efficacy of ticagrelor versus clopidogrel with respect to angiographic outcomes before and after PCI in the setting of acute coronary syndrome. - Background - Greater platelet inhibition has been associated with improved angiographic outcomes before and after percutaneous coronary intervention (PCI). Therefore, it was hypothesized that treatment with ticagrelor, which achieves more rapid, higher, and more consistent platelet inhibition, would be associated with improved angiographic outcomes when compared with those of clopidogrel treatment. - Methods - The angiographic cohort consists of 2,616 patients drawn from the 18,624-patient PLATO trial. Clopidogrel naïve or pre-treated patients were randomized to 180 mg of ticagrelor or 300 mg of clopidogrel (75 mg for clopidogrel pre-treated patients). PCI patients were administered, as per treatment group: 1) an additional 90 mg of ticagrelor if >24 h following the initial loading dose; or 2) an optional further 300 mg of clopidogrel or placebo (total 600 mg) prior to PCI. The substudy primary endpoint was the incidence of post-PCI TIMI (Thrombolysis In Myocardial Infarction) myocardial perfusion grade 3 (TMPG 3) among patients who received a study drug prior to PCI. - Results - In total, 21.3% of patients were pretreated with clopidogrel prior to randomization. There was a short time interval between randomization and PCI (median: 0.68 [interquartile range (IQR): 0.30 to 2.21] h) among all patients. Post-PCI TMPG 3 was similar between the ticagrelor and clopidogrel groups (47.1% vs. 46.9%; p = 0.96). Likewise, the following pre-PCI outcomes were similar in the ticagrelor and clopidogrel groups, respectively: TMPG 3 (30.5% vs. 31.2%), TIMI flow grade 3 (37.1% vs. 39.3%), corrected TIMI frame count (median: 100 vs. 71 frames), TIMI thrombus grade 0 (24.1% vs. 27.6%), minimum lumen diameter (median: 0.3 [IQR: 0.0 to 0.6] vs. 0.3 [IQR: 0.0 to 0.6] mm) and percentage of diameter stenosis (median: 89 [IQR: 78 to 100] vs. 89 [IQR: 77 to 100]). - Conclusions - Neither coronary flow nor myocardial perfusion, evaluated on coronary angiograms performed before or following PCI procedures within a few hours after the start of oral antiplatelet treatment in the setting of acute coronary syndromes, demonstrated a difference with ticagrelor versus clopidogrel. (A Comparison of Ticagrelor [AZD6140] and Clopidogrel in Patients With Acute Coronary Syndrome [PLATO]; NCT00391872)
Gesehen am 01.07.2021